2020
DOI: 10.31849/reila.v2i1.3960
|View full text |Cite
|
Sign up to set email alerts
|

Discourse Analysis in E-Learning-Based Course Using Moodle Platform: An Experimental Design

Abstract: The COVID-19 pandemic has caused educational institutions all over the world to migrate their teachings online. Since Indonesian government issued the SK Mendiknas No. 107/U/2001, educational institutions had to steadily integrate their learning process with technology. So, this study intends to investigate the effectiveness of using the open-source learning platforms known as Moodle in a selected university, Universitas Lancang Kuning (Unilak) in Indonesia. While multiple courses uses Moodle, this study selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 11 publications
2
28
0
1
Order By: Relevance
“…Unlike the traditional classroom, e-learning can provide access to the content an unlimited number of times. It also enables learners to access updated content anytime and anywhere (Putri, 2019;Putri et al, 2020). Also, e-learning is a way to provide quick delivery of the lesson and also reduces costs.…”
Section: Potentials To Contribute E-learning Implementationsmentioning
confidence: 99%
“…Unlike the traditional classroom, e-learning can provide access to the content an unlimited number of times. It also enables learners to access updated content anytime and anywhere (Putri, 2019;Putri et al, 2020). Also, e-learning is a way to provide quick delivery of the lesson and also reduces costs.…”
Section: Potentials To Contribute E-learning Implementationsmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, most higher education institutions had already started to allow students to use social media and other digital technologies to address their learning and research needs (their socialisation experience) (Annamalai, 2019;Mpungose, 2020a;Deng & Tavares, 2013;Henry et al, 2016;Madge et al, 2009). During the COVID-19 lockdown, universities have expanded their CMS platforms, such as Moodle, to ensure that teaching, learning, and research activities continue (Putri et al, 2020). There is a range of social and professional digital technologies available for students to use during the COVID-19 pandemic, and it is up to them to decide which ones are relevant for addressing their personal research needs.…”
Section: Personalisation Experiences Of Using Digital Technologies Anmentioning
confidence: 99%
“…Another study by Allo (2020) which was conducted in one of the private universities in Indonesia addressed that online learning is virtuous in this pandemic and confessed some recommendations from the college students' perspectives using online interviews related to the e-learning implementation. There was an experimental-study by Putri et al (2020), piloted in one of the private universities in Indonesia, that examined that the effectiveness of applying the open-source learning platform, namely Moodle in a designated university. The research showed that Moodle improved the learning of EFL university students effectively compared to normal lecture-style learning.…”
Section: Introductionmentioning
confidence: 99%